Decentralisation and land administration in the Upper West Region of Ghana : a spatial exploration of law in development - Kunbuor, Benjamin Bewa-Nyog (2000)
Decentralisation for local community development has become the new paradigm of development discourse in Ghana in the present times. There is currently an elaborate legal framework in Ghana on decentralisation as a means for addressing local community development. The role of law in development is therefore implicated in the discourse. This study raises provocative, startling and challenging questions not only on the decentralisation programme, but the appropriate theoretical framework for reading the role of law in development. The study argues that decentralisation in Ghana is a spatial strategy of the state for addressing the crisis of its political economy and not one necessarily for local community development. Taking its starting point in land administration in the Upper West Region of Ghana (predominantly agrarian communities), the study explores how the objectives of decentralisation in Ghana address the subjectivity of development needs of local communities in Ghana. The study's contention is that the legal regime of the decentralisation programme and its praxis fail to address a pertinent development concern (land) of the Upper West communities. The study argues that if local community development were the object of the programme, it would perforce address the problematic of land administration that is an important concern for predominantly subsistence farming communities. The study also demonstrates how a spatial reading of social phenomenon provides critical insights to an understanding of the role of law in development. The study is based on a field study conducted in Ghana and among the communities of the Upper West Region, through interviews with officials of institutions, traditional authorities and civil society organisations. The interviews were complemented by written primary and secondary sources. Primary sources include documents from the National Archives in Ghana and from decentralised institutions in the Upper West Region. Secondary sources include unpublished essays and theses, books, articles, reported cases in the Ghana Law Reports, unreported and/or pending cases in the Ghanaian courts.